SOCIALIZATION OF GADGET MONITORING IN CHILDREN - Wiryany, Detya; Humaedi, Muhammad Arfan; Maulana, Niko Nur; Muliawan, Riyan Candra; Aurenevia, Shafira; Sabila, Khansa (Inaba of Community Services Journal, 2022)
Parent-child communication with a "child-friendly" parenting style is empathetic and full of love. This is important because from an early age children already feel that they are accepted, loved, and valued for their existence. With positive parenting, children will form "basic trust" which will make them a strong foundation of self-confidence. Self-confidence is very important for the development of a steady body and soul, full of confidence, and full of love during its development. The basic principle of applying positive parenting is trying to make parents actively listen to every child's conversation, respect the child's opinion, give appreciation to children's behavior that is considered good, and gradually. Applying discipline according to the stages of the child's mental development. Talking about today's technology which is increasingly sophisticated, namely the use of devices that are easily practiced by children today, therefore parents must also provide supervision when giving devices to their children, so that their children can control the use of devices in a good way and effective. This activity was carried out to increase parental awareness in supervising the use of devices by children.